Pengaruh Pijat Perineum Terhadap Kejadian Ruptur Perineum Pada Ibu Primigravida di Klinik Bersalin Bidan Yorina Merukh - Nurul Jannah Sangadji; Lisa Ardiningtyas; Winarsih Mokoagow (Jurnal Ners, 2026)
Perineal rupture is one of the most common complications during normal childbirth, particularly among primigravida mothers whose perineal tissues have lower elasticity. Perineal massage is considered a non-pharmacological intervention that can help increase perineal elasticity and reduce the risk of birth canal lacerations. This study aimed to determine the effect of perineal massage on the incidence of perineal rupture among primigravida mothers at the Yorina Merukh Midwifery Clinic. This research employed a quasi-experimental design with two intervention groups, consisting of 5-minute and 10-minute perineal massage durations. All primigravida mothers who met the inclusion criteria were selected as samples using a total sampling technique. Data were collected through direct observation during labor using structured observation sheets. Univariate and bivariate analyses were conducted to assess differences in the incidence of perineal rupture based on the duration of perineal massage. The results showed a difference in the incidence of perineal rupture between the two groups, with the 10-minute perineal massage demonstrating greater effectiveness in reducing perineal rupture compared to the 5-minute massage. These findings indicate that perineal massage contributes to increased tissue elasticity, thereby minimizing the risk of rupture during childbirth. In conclusion, perineal massage is a beneficial intervention and can be recommended as a preventive measure to reduce perineal rupture among primigravida mothers.